Frequency discrimination in rats measured with tone-step stimuli and discrete pure tones - Sloan, Andrew M. (2009)
Two modified go/no-go tasks are compared for the measurement of frequency discrimination in albino rats. The first task required detection of an instantaneous, phase-matched frequency change, called a “tone-step,” within a continuous reference tone. The more traditional second task required detection of a frequency change between repetitions of a reference sequence of repeating discrete tones. For each task frequency difference limens were measured over a range of reference frequencies from 2.31 to 27.7 kHz at 60 dB sound pressure level, with both upward and downward frequency shifts. All 24 subjects quickly learned the “tone-step” task to criterion, but only 13 could also learn the discrete tone task. Subjects’ performance at either task generally improved with increasing reference frequency, and in both tasks upward frequency change thresholds were significantly higher than thresholds for downward changes. Overall mean Weber ratios were 1.73±0.27% for the “tone-step” task and 2.76±0.29% for the discrete tone task. However, subjects’ performance on the “tone-step” task was not correlated with subsequent performance on the discrete tone task. We suggest that the lack of correspondence between tasks might be due to frequency discrimination processes interacting with short-term memory traces during inter-tone intervals in the discrete tone task.